Estimasi Cadangan Karbon Komunitas Mangrove Dusun Keranji, Desa Paremas, Lombok Timur - Haykal, Muhammad; Harman, Carlen Aufa; ZA, Siti Asiah; Buhari, Nurliah; Lestariningsih, Wiwid Andriyani; Damayanti, Ayu Adhita; Rahman, Ibadur (Program Studi Ilmu Kelautan, Jurusan Perikanan dan Ilmu Kelautan, Fakultas Pertanian, Universitas Mataram, 2025)
Carbon dioxide is one of the greenhouse gases that reflects sunlight radiation. Mangrove trees have the ability to absorb and store carbon in the air, so the existence of a mangrove tree could be one of the solutions to the global warming problem. This research aims to find out the amount of carbon reserves in the mangrove communities that exist in Keranji Hamlet, Paremas, East Lombok. The survey method used in this research is an explorative descriptive method that will make it easier to understand and interpret the data. To determine the stock of mangrove carbon, data is needed that will influence the carbon content such as diameter, density, type and percentage of the coverage of the mangrove. In this study, six species of mangroves were identified: Avicennia alba, A. marina, Rhizophora apiculata, R. mucronata, R. stylosa, and Sonneratia alba. The average density value obtained is 988,889 ind/ha so it is known that the mangrove forests of Keranji Hamlet, Paremas, Jerowaru, East Lombok have rare cover conditions based on standard quality of forest damage. The average diameter of the mangrove tree is the highest value at transec 2, so the highest carbon reserve value is found at transec 2, whether it's root or rod. The average estimated reserve is spread out at 104.96 tons/ha of rod carbon and at 56.05 tons/he of root carbon that marks the rod carbon belonging to the high category and the rod carb belongs to the medium category.